IgG4 Autoantibodies in Organ-Specific Autoimmunopathies: Reviewing Class Switching, Antibody-Producing Cells, and Specific Immunotherapies - Koneczny, Inga; Tzartos, John; Mané-Damas, Marina; Yilmaz, Vuslat; Huijbers, Maartje G.; Lazaridis, Konstantinos; Höftberger, Romana; Tüzün, Erdem; Martinez-Martinez, Pilar; Tzartos, Socrates; Leypoldt, Frank (Frontiers in Immunology, 2022)
Organ-specific autoimmunity is often characterized by autoantibodies targeting proteins expressed in the affected tissue. A subgroup of autoimmunopathies has recently emerged that is characterized by predominant autoantibodies of the IgG4 subclass (IgG4-autoimmune diseases; IgG4-AID). This group includes pemphigus vulgaris, thrombotic thrombocytopenic purpura , subtypes of autoimmune encephalitis, inflammatory neuropathies, myasthenia gravis and membranous nephropathy. Although the associated autoantibodies target specific antigens in different organs and thus cause diverse syndromes and diseases, they share surprising similarities in genetic predisposition, disease mechanisms, clinical course and response to therapies. Importantly, IgG4-AID differ significantly from diseases associated with IgG1 autoantibodies targeting the same organ. This may be due to the unique functional characteristics of IgG4 autoantibodies (e.g. anti-inflammatory and functionally monovalent) that affect how the antibodies cause disease, and the differential response to immunotherapies of the IgG4 producing B cells/plasmablasts. These clinical and pathophysiological clues give important insight in the immunopathogenesis of IgG4-AID. Understanding IgG4 immunobiology is a key step towards the development of novel, IgG4 specific treatments. In this review we therefore summarize current knowledge on IgG4 regulation, the relevance of class switching in the context of health and disease, describe the cellular mechanisms involved in IgG4 production and provide an overview of treatment responses in IgG4-AID.